A PTFE modified separation membrane for fluid purification and preparation method thereof
By adding carbon fiber and nanosilver to the PTFE membrane and using modification treatment and laser etching techniques, a modified membrane matrix with a hierarchical structure was constructed, which solved the problem of small flux, short service life and low-temperature freezing and blockage of PTFE filter membrane. Problem, superhydrophobic, self-cleaning and antibacterial properties have been achieved.
Patent Information
- Application Number
- CN202411297687.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-23
- Filing Date
- 2024-09-18
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The membrane flux of PTFE filter membrane is small, has a short service life, and is prone to freezing and blocking under low temperature conditions, affecting filtration performance.
By adding carbon fiber and nanosilver to the PTFE film, and using ammonium salt solution modification treatment, bidirectional stretching and heat treatment, gas laser etching and other technologies, a modified film matrix with a hierarchical structure is constructed to enhance the hydrophobicity and antibacteriality of the film. and corrosion resistance.
The superhydrophobicity, self-cleaning and anti-icing properties of PTFE film are achieved, which enhances the antibacteriality and corrosion resistance of the film, extends the service life of the film and increases the membrane flux.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the field of separation membrane modification, and in particular relates to a PTFE modified separation membrane for fluid purification and a preparation method thereof. Background Art
[0002] Membrane materials are key components of the filtration system and play a decisive role in the entire separation process. Polytetrafluoroethylene (PTFE) membranes are naturally hydrophobic and can pass through moist air or other gases while retaining the water phase even under low pressure differential conditions. They have extremely strong chemical compatibility and can be used for filtering organic solvents and highly corrosive chemicals. However, they still have limitations in application. For example, continuous low-temperature rain and snow weather can easily cause freezing of filtration facilities in cold northern regions. When the temperature is below freezing, due to large local temperature changes and uneven flow of tap water, local crystal nuclei grow rapidly, thereby blocking the filter membrane, reducing membrane flux and shortening life.
[0003] Although the industry has made great progress in the preparation of PTFE membranes, for example, patent CN107321198A discloses an inorganic nanomaterial and PTFE hybrid hydrophobic membrane for seawater desalination, the industrialization and application technology of PTFE membranes are still immature. In the processing of PTFE membranes, there are still problems such as difficulty in controlling the micropore size, low porosity, and chaotic pore structure. In order to expand its application field, it is urgent to find a reasonable and effective preparation method. Summary of the invention
[0004] Based on the above content, in order to solve the problems of low flux and short service life of PTFE filter membrane, the present invention proposes a PTFE modified separation membrane for fluid purification and a preparation method thereof.
[0005] The purpose of the present invention is: 1. To realize super-hydrophobic PTFE membrane and ensure its high porosity.
[0006] 2. Make the PTFE membrane self-cleanable and anti-icing.
[0007] 3. Enhance the antibacterial and corrosion resistance of PTFE membrane.
[0008] To achieve the above objectives, the present invention adopts the following technical solutions.
[0009] A method for preparing a PTFE modified separation membrane for fluid purification comprises: 1) taking a raw material and molding it into a precursor membrane.
[0010] 2) The precursor film is modified with an ammonium salt solution to obtain a modified film.
[0011] 3) The modified membrane is preheated, biaxially stretched and heat treated, and then gas laser etching is performed to obtain a PTFE modified separation membrane.
[0012] Preferably, the raw materials in step 1) include polytetrafluoroethylene, carbon fiber, silver powder and an additive; the additive is an isoparaffin solvent.
[0013] Preferably, the polytetrafluoroethylene, carbon fiber and silver powder are mixed in a mass ratio of 10: (0.5-1.0): (0.1-0.5); the isoparaffin solvent is Isopar H auxiliary agent, and the dosage is 0.1-0.3 g / g polytetrafluoroethylene.
[0014] Preferably, in step 1), the raw materials are mixed, heated to melt at 330-370° C., and then compression molded at a pressure of 2.4-7.0 MPa.
[0015] Preferably, before the precursor film is modified in step 2), 0.2-0.4 mol / L aniline solution and water are mixed in a volume ratio of 1:(20-30) to form a mixed solution, and the precursor film is infiltrated with the mixed solution.
[0016] Preferably, the ammonium salt solution in step 2) is 0.40-0.58 g / mL ammonium persulfate solution.
[0017] Preferably, the preheating temperature in step 3) is 140-160°C and the temperature is kept constant for 15-25 min; the biaxial stretching process in step 3) is carried out at 200-240°C, and the biaxial stretching in the transverse and longitudinal directions is carried out at a rate of 230-280 mm / min, and the stretching ratio is ≤4 times.
[0018] Preferably, the heat treatment in step 3) is performed at 240-280° C. for 10-20 min.
[0019] Preferably, the gas laser etching process in step 3) is: processing the film with a 10-20 W carbon dioxide laser; the control parameters during the gas laser etching process are: laser scanning speed of 1-5 mm / min, scanning spacing of 3-8 μm, processing accuracy of ±20 μm, repetition frequency of 1-5 kHz, nitrogen and / or argon gas assistance, and Z-axis offset of -5-0 mm.
[0020] A PTFE modified separation membrane for fluid purification.
[0021] Preferably, the PTFE modified separation membrane is suitable for filtering and purifying low-temperature water at 2 to 4°C.
[0022] In the technical solution of the present invention, carbon fiber and nanosilver are used on the basis of PTFE, and the construction of a modified membrane matrix with a hierarchical structure is successfully realized. Although minerals in water bodies can bring people the constant elements needed for daily life, excessive minerals in over-mineralized water bodies will affect health, and are not suitable for irrigation of soil and industrial applications with control indicators for hardness in water. The membrane material prepared by the present invention has high precision, macroscopically reduces the content of calcium salts and magnesium salts, and improves water quality. Adding carbon fiber can increase the elastic modulus of the membrane and reduce the wear rate. With the increase of carbon fiber content, the tensile resistance of the PTFE membrane is enhanced. The PTFE membrane doped with 5-10% carbon fiber is stable under stress conditions, and the membrane shows good surface wear resistance; nanosilver can enhance the antibacterial property of the membrane, and the synergistic effect of carbon fiber and nanosilver can extend the service life of the PTFE membrane. According to the research of those skilled in the art, after 50 times of mechanical grinding, the contact angle between the surface and water of the composite PTFE membrane can be maintained at 140°, so that it has higher wear resistance. However, merely maintaining the contact angle between the PTFE membrane surface and water at above 140° is not sufficient for effective water-oil separation applications, so the present invention further modifies the composite membrane.
[0023] In the present invention, fluorine atoms repel each other, twist in the plane, present a "helical shape" along the carbon chain, and are tightly wrapped outside the carbon chain skeleton, thereby preventing nanosilver from penetrating the PTFE membrane and being introduced into the water, preventing external impurities from destroying the carbon chain, and enhancing the corrosion resistance and antibacterial properties of the PTFE membrane. In order to further enhance the hydrophobicity of the PTFE membrane, the present invention introduces the structure of polyaniline through in-situ polymerization to further increase the roughness of the membrane surface. According to the research of those skilled in the art, under the conditions of low temperature and low concentration, small molecular weight polyaniline is generated, and the polyaniline is attached to the surface of the PTFE composite membrane in the form of particles, and the fluorine atom provides high electronegativity, so that the fluorine atom and the amino group on the aniline form hydrogen bonds. When the concentration of the aniline solution is low, the amount of aniline in situ polymerization is small, and the granular polyaniline makes the PTFE composite membrane less rough, so that the surface contact angle with water is also small; when the concentration of the aniline solution is higher than 0.15 mol / L, the aniline polymerization rate increases, the amount of polyaniline can be significantly increased, and it tends to be fibrous, which is enough to cover the PTFE membrane and increase the contact angle of its surface with water. However, when the concentration is too high, it is easy to produce partial agglomeration in the form of agglomeration, and the growth distribution is uneven. Therefore, the present invention controls the concentration of the aniline solution to 0.2-0.4 mol / L. At the same time, due to the complex fiber layers on the composite membrane, a three-dimensional network structure is formed. This structure acts as a barrier to enhance the corrosion resistance and antibacterial properties of the membrane, and at the same time, the membrane forms a micro-elastic body, so that it is not easy to be damaged and aged after freezing, and can effectively maintain the original performance.
[0024] In addition, the present invention uses Isopar H auxiliary agent, which is helpful to obtain a film with higher porosity during compression molding, and can be removed during preheating. Then, the film is further heated and sintered. The sintering temperature should be higher than the melting point of PTFE and lower than the decomposition temperature of PTFE. A small amount of PTFE is remelted by sintering, so that the orientation of PTFE is rearranged, thereby connecting the internal structure, improving the tensile strength of the PTFE film, and avoiding the subsequent film from breaking during stretching. In order to increase the porosity, improve the membrane flux, and obtain a uniform high-porosity film, the present invention stretches the film while hot, and the porosity of the film increases with the increase of the stretching multiple during stretching. The film is stretched while hot so that it is evenly expanded and easier to be stretched, and the film material is avoided from being too thin. The present invention controls its stretching ratio, and then sintering again plays a shaping role.
[0025] Finally, laser etching uses laser irradiation to heat the membrane surface and heat it up, so that phase changes such as melting and evaporation occur. The present invention uses CO2 laser to process PTFE membrane, and the surface roughness structure is constructed so that the contact angle between the surface of PTFE membrane and water is greater than 160°, reaching the super-hydrophobic standard, that is, the contact angle between the surface and water is greater than 150°, and the sliding angle is less than 10°. Laser etching can accurately control the size and volume of pores. During processing, special attention should be paid to the laser power. When the power is greater than 20 W, the excessive power causes a large amount of surface material to be removed and a pit-like structure to appear, which in turn reduces the roughness of the membrane surface, and the contact angle continues to decrease with the increase of power.
[0026] The core of the present invention is to increase the contact angle between the PTFE membrane surface and water, reduce the surface free energy of the membrane, the purpose is to reduce the wetting rate of pure water, and there are two methods to reduce the wetting rate of the membrane, namely, to improve the hydrophobicity of the membrane and reduce the pore size of the membrane, but reducing the pore size of the membrane will reduce the membrane flux, so the present invention realizes super-hydrophobic membrane by increasing the method for membrane hydrophobicity, when water vapor passes through the PTFE membrane and condenses on the cold side, grease, bacteria, organic matter, etc. can be isolated on the hot side, thereby realizing water-oil separation and purification, because the rough structure of the super-hydrophobic membrane surface increases the gap between the membrane and the pure water, increases the effective evaporation area, therefore without increasing the possibility of membrane pore wetting without increasing additional mass transfer resistance, the membrane flux is high, and when the filtering system is not used, due to the rough structure of the membrane surface, it has certain self-cleaning and anti-icing properties, and the time of freezing of the filter membrane surface is extended during low temperature weather.
[0027] The beneficial effects of the present invention are as follows: (1) The PTFE modified separation membrane obtained by the present invention presents a three-dimensional network structure, and the contact angle between the surface of the PTFE membrane and water is greater than 155°, and has super hydrophobic properties.
[0028] (2) The surface of the PTFE modified separation membrane obtained in the present invention has a micro-rough structure, and when a droplet hits the super-hydrophobic surface, its freezing is delayed.
[0029] (3) The PTFE modified separation membrane obtained by the present invention contains Ag, and air is retained in the grooves of the rough structure, forming an air layer. The air layer can prevent the substrate from directly contacting the corrosive medium, increase the resistance of the corrosive medium to infiltrate the surface of the substrate, and thus greatly improve the corrosion resistance and antibacterial properties. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0031] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0032] Unless otherwise specified, the average particle size of the polytetrafluoroethylene particles used in the embodiments of the present invention is ≥350 μm.
[0033] Unless otherwise specified, the carbon fiber used in the embodiments of the present invention is chopped carbon fiber.
[0034] Unless otherwise specified, the purity of the nano-Ag used in the embodiments of the present invention is 96.5 wt %.
[0035] Unless otherwise specified, the purity of the Isopar H additive used in the embodiments of the present invention is 99.6 wt%.
[0036] Unless otherwise specified, the PTFE modified separation membrane obtained in the examples of the present invention has a thickness of 200 μm and a width of 500 mm.
[0037] Example 1: A method for preparing a PTFE-modified separation membrane for fluid purification, the method comprising: 1) melting 10 g of polytetrafluoroethylene particles, 0.8 g of carbon fiber and 0.3 g of nano-Ag at 360°C, adding 2 g of Isopar H additive, compression molding at a pressure of 5 MPa, washing with ethanol and distilled water and drying respectively, to obtain a precursor membrane.
[0038] 2) Prepare 0.3 mol / L aniline ethanol solution, add 0.83 mL aniline solution into 25 mL water, stir magnetically at -2 °C for 24 h to obtain a mixed solution, soak the precursor film in the mixed solution, slowly add 0.5 g / mL ammonium persulfate solution, stir and let stand, wash with ethanol and distilled water respectively and dry to obtain a modified membrane.
[0039] 3) The modified membrane was kept at a constant temperature of 160 ℃ for 15 min, and then the temperature was continued to rise to 200 ℃ for 2 h. The membrane was stretched at a constant temperature of 240 ℃ while hot, and stretched transversely and longitudinally at a rate of 250 mm / min, respectively, with the membrane stretching ratio controlled at 2.4:1. The membrane was then fixed at 260 ℃ for 15 min, laser etched, cleaned with acetone and dried to obtain a PTFE modified separation membrane.
[0040] The above laser etching is as follows: an Epilog CO2 laser machine is used to process the film, and the laser power is set to 10 W with adjustable pulse width, the scanning speed is 3 mm / min, the scanning interval is 5 μm, the processing accuracy is ±20 μm, the repetition frequency is 3 kHz, argon gas is assisted, and the Z-axis offset is 0 mm.
[0041] The performance test of the PTFE modified separation membrane obtained in this example is as follows.
[0042] 1. Tensile performance test: Test in the warp and weft directions respectively. According to JIS-C-2151 and ASTM-D-882 standards, clamp the film with a pneumatic clamp and pull the film at a speed of 200 mm / min to measure the strength of the film when it is torn at the maximum test force. The value obtained by dividing the tensile load by the cross-sectional area of the sample is taken as the smaller value of the warp and weft directions.
[0043] 2. Aperture and porosity test: The pore size and porosity of the membrane material are measured by the fully automatic specific surface area and pore size analyzer V-Sorb X800 (SM). 20 test points are selected to calculate the average pore size.
[0044] 3. Membrane flux test: Use membrane materials to separate two independent airflow systems, one side is flowing oxygen, and the other side is flowing dry nitrogen. The oxygen side has a higher partial pressure. The concentration difference drives the oxygen to pass through the membrane and is sent to the sensor by the nitrogen flow. The sensor accurately measures the amount of oxygen carried in the nitrogen flow, thereby calculating the oxygen permeability of the material. The oxygen permeability directly measured by the sensor method and uncorrected, the calculation formula for oxygen permeability provided by ISO 15105-2 is: ; The recording unit is converted to mm / s (0.1MPa test condition).
[0045] Contact angle test: The contact angle between the surface and water is measured by SITA high-precision surface tester. 20 test points are taken to calculate the average contact angle.
[0046] 5. Antibacterial performance test: Liquid was prepared with Staphylococcus aureus and Klebsiella pneumoniae, and membrane distillation experiments were performed to determine the number of live bacteria in the filtrate and calculate the antibacterial rate.
[0047] 6. Characterization of filtered hard water: Prepare a test solution with a hardness of 1500 mg / L, and allow the test solution to flow through the separation membrane at a flux of 15 mm / s for 24 hours. After 24 hours, characterize the test solution that has passed through the separation membrane according to the national standard GB 5749-2006.
[0048] The results are as follows.
[0049]
[0050] According to the results in the above table, this example successfully achieved a hydrophobic PTFE modified separation membrane with strong tensile strength, high porosity, considerable membrane flux, and antibacterial properties. The PTFE modified separation membrane obtained in this example has a certain inhibitory effect on Klebsiella pneumoniae. It can be seen that the PTFE modified separation membrane prepared by the present invention has a very broad prospect for fluid purification. It can be used for sterilization and purification of fluids and filtration and removal of a large number of impurities. Its pore size reaches the nanometer level and can also filter some molecular-level pollutants. It is of great significance for fluid purification. The water body is filtered through the membrane material, and the water quality is softened, which meets the national standards for drinking water. In addition, compared with conventional PTFE filter membranes, the oxygen permeability of the present invention is significantly improved, which is higher than the conventional 15-18 mm / s air permeability of high-precision PTFE filter membranes.
[0051] In addition, the prepared PTFE modified separation membrane for fluid purification was also subjected to a freezing test. After the sample membrane was ultrasonically immersed in deionized water for 15 seconds, it was taken out and immediately transferred to a -40 ℃ freezer. The initial freezing time (initial freezing) and complete freezing time (final freezing) of the surface were observed and recorded. Ten sample membranes were randomly selected and each sample membrane was tested 20 times in total, and the average values were recorded as follows.
[0052]
[0053] It can be clearly seen from the above characterization results that the PTFE modified separation membrane prepared in the present invention has a very excellent ability to prevent supercooling and icing, and has significantly better use effect than conventional PTFE membranes when used in northern regions.
[0054] Example 2: A method for preparing a PTFE-modified separation membrane for fluid purification, the method comprising: 1) melting 10 g of polytetrafluoroethylene particles, 0.8 g of carbon fiber and 0.3 g of nano-Ag at 360°C, adding 2 g of Isopar H additive, compression molding at a pressure of 5 MPa, washing with ethanol and distilled water and drying respectively to obtain a precursor membrane; the above-mentioned carbon fiber has a length of 7 μm and the nano-Ag particle size is 30 nm.
[0055] 2) Prepare 0.3 mol / L aniline solution, add 1.03 mL of aniline solution into 25 mL of water, stir magnetically at -2 °C for 24 h to obtain a mixed solution, soak the precursor film in the mixed solution, slowly add 0.5 g / mL ammonium persulfate solution, stir and let stand, wash with ethanol and distilled water respectively and dry to obtain a modified membrane.
[0056] 3) The modified membrane was kept at a constant temperature of 160 ℃ for 15 min, and then the temperature was continued to rise to 200 ℃ for 2 h. The membrane was stretched at a constant temperature of 240 ℃ while hot, and stretched transversely and longitudinally at a rate of 250 mm / min, respectively, with the membrane stretching ratio controlled at 2.4:1. The membrane was then fixed at 260 ℃ for 15 min, laser etched, cleaned with acetone and dried to obtain a PTFE modified separation membrane.
[0057] The above laser etching is as follows: an Epilog CO2 laser machine is used to process the film, and the laser power is set to 10 W with adjustable pulse width, the scanning speed is 3 mm / min, the scanning interval is 5 μm, the processing accuracy is ±20 μm, the repetition frequency is 3 kHz, argon gas is assisted, and the Z-axis offset is 0 mm.
[0058] The PTFE modified separation membrane obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.
[0059]
[0060] According to the results in the above table, in this example, the amount of aniline solution was increased to obtain a PTFE membrane with better tensile resistance and higher membrane flux. More fluorine atoms were wrapped around the carbon chain skeleton, providing high electronegativity and forming more hydrogen bonds, further enhancing the antibacterial property of the PTFE membrane. At the same time, the amount of aniline in situ polymerization was larger, and the fibrous polyaniline made the PTFE composite membrane rough, thereby increasing the contact angle between the surface and water and improving the hydrophobicity.
[0061] In addition, the freezing test was also carried out. After 20 tests, the average initial setting time of the sample film was 50.2 s, and the average final setting time was 197.6 s. It also showed excellent anti-freezing performance.
[0062] Example 3: A method for preparing a PTFE-modified separation membrane for fluid purification, the method comprising: 1) melting 10 g of polytetrafluoroethylene particles, 0.8 g of carbon fiber and 0.3 g of nano-Ag at 360°C, adding 2 g of Isopar H additive, compression molding at a pressure of 5 MPa, washing with ethanol and distilled water and drying respectively to obtain a precursor membrane; the above-mentioned carbon fiber has a length of 7 μm and the nano-Ag particle size is 30 nm.
[0063] 2) Prepare 0.3 mol / L aniline solution, add 1.25 mL of aniline solution into 25 mL of water, and stir magnetically at -2 °C for 24 h to obtain a mixed solution. Take the precursor film and immerse it in the mixed solution. Slowly add 0.5 g / mL ammonium persulfate solution, stir magnetically at below 0 °C and let it stand for 24 h. Wash it with ethanol and distilled water respectively and dry it to obtain a modified membrane.
[0064] 3) The modified membrane was kept at a constant temperature of 160 ℃ for 15 min, and then the temperature was continued to rise to 200 ℃ for 2 h. The membrane was stretched at a constant temperature of 240 ℃ while hot, and stretched transversely and longitudinally at a rate of 250 mm / min, respectively, with the membrane stretching ratio controlled at 2.4:1. The membrane was then fixed at 260 ℃ for 15 min, laser etched, cleaned with acetone and dried to obtain a PTFE modified separation membrane.
[0065] The above laser etching is as follows: an Epilog CO2 laser machine is used to process the film, and the laser power is set to 10 W with adjustable pulse width, the scanning speed is 3 mm / min, the scanning interval is 5 μm, the processing accuracy is ±20 μm, the repetition frequency is 3 kHz, argon gas is assisted, and the Z-axis offset is 0 mm.
[0066] The PTFE modified separation membrane obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.
[0067]
[0068] According to the results in the above table, this example further increased the amount of aniline solution, and the tensile strength, porosity, membrane flux and other aspects of the PTFE modified separation membrane were improved, but the degree of improvement was small, and the PTFE membrane modified with excessive polyaniline had poor stability.
[0069] The PTFE modified separation membrane obtained in this example was further subjected to mechanical friction 50 times, and its contact angle was measured again, and the result was 153°±1°, confirming that the PTFE membrane modified with excessive polyaniline had poor stability.
[0070] In addition, the freezing test was also carried out. After 20 tests, the average initial setting time of the sample film was 50.6 s, and the average final setting time was 198.0 s. It also showed excellent anti-freezing performance.
[0071] Comparative Example 1: A method for preparing a PTFE-modified separation membrane for fluid purification, the method comprising: 1) melting 10 g of polytetrafluoroethylene particles, 0.2 g of carbon fiber and 0.3 g of nano-Ag at 360°C, adding 2 g of Isopar H additive, compression molding at a pressure of 5 MPa, washing with ethanol and distilled water and drying respectively to obtain a precursor membrane; the above-mentioned carbon fiber has a length of 7 μm and the nano-Ag particle size is 30 nm.
[0072] 2) Prepare 0.3 mol / L aniline solution, add 1.03 mL of aniline solution into 25 mL of water, and stir magnetically at -2 °C for 24 h to obtain a mixed solution. Take the precursor film and immerse it in the mixed solution. Slowly add 0.5 g / mL ammonium persulfate solution, stir and let it stand, wash with ethanol and distilled water respectively, and dry to obtain a modified membrane.
[0073] 3) The modified membrane was kept at a constant temperature of 160 ℃ for 15 min, and then the temperature was continued to rise to 200 ℃ for 2 h. The membrane was stretched at a constant temperature of 240 ℃ while hot, and stretched transversely and longitudinally at a rate of 250 mm / min, respectively, with the membrane stretching ratio controlled at 2.4:1. The membrane was then fixed at 260 ℃ for 15 min, laser etched, cleaned with acetone and dried to obtain a PTFE modified separation membrane.
[0074] The above laser etching is as follows: an Epilog CO2 laser machine is used to process the film, and the laser power is set to 10 W with adjustable pulse width, the scanning speed is 3 mm / min, the scanning interval is 5 μm, the processing accuracy is ±20 μm, the repetition frequency is 3 kHz, argon gas is assisted, and the Z-axis offset is 0 mm.
[0075] The PTFE modified separation membrane obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.
[0076]
[0077] According to the results in the above table, the amount of carbon fiber used was reduced in this example. Although a hydrophobic PTFE-modified separation membrane with high porosity, considerable membrane flux and antibacterial properties was still obtained, it can be seen that the tensile strength of the PTFE-modified separation membrane decreased, and the hardness of the test liquid after testing was still relatively high.
[0078] The PTFE modified separation membrane obtained in this example was further mechanically rubbed 50 times, and its contact angle was measured again, and the result was 149°±1°, which confirmed that the addition of carbon fiber can increase the elastic modulus of the membrane and reduce the wear rate. Too little carbon fiber is not conducive to the long-term function of the PTFE modified separation membrane.
[0079] In addition, freezing tests were also conducted. After 20 tests, the average initial setting time of the sample film was 48.0 s, and the average final setting time was 195.1 s, which also showed excellent antifreeze performance.
[0080] Comparative Example 2: A method for preparing a PTFE-modified separation membrane for fluid purification, the method comprising: 1) melting 10 g of polytetrafluoroethylene particles, 0.8 g of carbon fiber and 0.3 g of nano-Ag at 360°C, adding 2 g of Isopar H additive, compression molding at a pressure of 5 MPa, washing with ethanol and distilled water and drying respectively to obtain a precursor membrane; the above-mentioned carbon fiber has a length of 7 μm and the nano-Ag particle size is 30 nm.
[0081] 2) Prepare 0.3 mol / L aniline solution, add 1.03 mL of aniline solution into 25 mL of water, and stir magnetically at -2 °C for 24 h to obtain a mixed solution. Take the precursor film and immerse it in the mixed solution. Slowly add 0.5 g / mL ammonium persulfate solution, stir and let it stand, wash with ethanol and distilled water respectively, and dry to obtain a modified membrane.
[0082] 3) The modified membrane was kept at a constant temperature of 160 ℃ for 15 min, and then the temperature was continued to rise to 200 ℃ for 2 h. The membrane was stretched at a constant temperature of 240 ℃ while hot, and stretched transversely and longitudinally at a rate of 250 mm / min, respectively, with the membrane stretching ratio controlled at 2.4:1. The membrane was then fixed at 260 ℃ for 15 min, laser etched, cleaned with acetone and dried to obtain a PTFE modified separation membrane.
[0083] The above laser etching is as follows: the film is processed using an Epilog CO2 laser machine, and the laser power is set to 25 W with adjustable pulse width, the scanning speed is 3 mm / min, the scanning interval is 5 μm, the processing accuracy is ±20 μm, the repetition frequency is 3 kHz, argon gas is assisted, and the Z-axis offset is 0 mm.
[0084] The PTFE modified separation membrane obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.
[0085]
[0086] According to the results in the above table, in this example, a laser with too high power was used to etch the membrane surface. The excessive power resulted in a large amount of surface material being removed and a pit-like structure appearing, which in turn reduced the micro-roughness of the membrane surface. The contact angle decreased with increasing power, and the membrane material did not meet the superhydrophobic standard, that is, the contact angle between the surface and water was greater than 150° and the sliding angle was less than 10°. Due to the excessive pit-like structures in the membrane material, the tensile resistance of the PTFE modified separation membrane obtained in this example was greatly reduced. The excessively large pore size also destroyed the antibacterial property of the membrane material, limiting its application.
[0087] In addition, the freezing test was also carried out. The average initial setting time of the first time was 42.9 s, and the average final setting time was 159.7 s. After 20 tests, the average initial setting time of the sample film was 39.1 s, and the average final setting time was 152.3 s. Compared with the example, it can be seen that the antifreeze performance of the sample film prepared in this example has a very significant decrease, but it can be seen that its antifreeze performance retention ability is still relatively good.
[0088] Comparative Example 3: A method for preparing a PTFE-modified separation membrane for fluid purification, the method comprising: 1) melting 10 g of polytetrafluoroethylene particles, 0.8 g of carbon fiber and 0.3 g of nano-Ag at 360°C, adding 2 g of Isopar H additive, compression molding at a pressure of 5 MPa, washing with ethanol and distilled water and drying respectively to obtain a precursor membrane; the above-mentioned carbon fiber has a length of 7 μm and a nano-Ag particle size of 30 nm.
[0089] 2) The precursor membrane was kept at a constant temperature of 160 °C for 15 min, and then the temperature was continued to rise to 200 °C for 2 h. The membrane was stretched at a constant temperature of 240 °C while hot, and stretched transversely and longitudinally at a rate of 250 mm / min, respectively, with the membrane stretching ratio controlled at 2.4:1. The membrane was then fixed at 260 °C for 15 min, laser etched, cleaned with acetone and dried to obtain a PTFE modified separation membrane.
[0090] The above laser etching is as follows: an Epilog CO2 laser machine is used to process the film, and the laser power is set to 10 W with adjustable pulse width, the scanning speed is 3 mm / min, the scanning interval is 5 μm, the processing accuracy is ±20 μm, the repetition frequency is 3 kHz, argon gas is assisted, and the Z-axis offset is 0 mm.
[0091] The PTFE modified separation membrane obtained in this example was subjected to the same performance test as in Example 1, and the results are as follows.
[0092]
[0093] It can be clearly seen from the above test results that the mechanical properties, porosity, oxygen flow rate and antibacterial properties of the membrane material after polyurethane modification treatment are greatly affected, and the elongation at break in the tensile test is significantly reduced. It can be seen that the formation of a three-dimensional network structure has a great influence on all aspects of the material performance.
[0094] In addition, the freezing test was also carried out. The average value of the first initial setting time was 36.5 s, and the average value of the final setting time was 153.1 s. After 20 tests, the average value of the initial setting time of the sample film was 16.8 s, and the average value of the final setting time was 42.9 s. It can be seen that although the sample film prepared in this example has a relatively good antifreeze effect in the early stage, the antifreeze effect decreases rapidly in the freezing test, which shows that it has a more significant freezing aging phenomenon. It can be seen from this that, for the present invention, the micro-elastomer formed by the three-dimensional network structure has a very significant effect on improving the antifreeze performance and antifreeze aging performance of the PTFE membrane.
[0095] Comparative Example 4: A commercially available PTFE membrane was selected. This brand of PTFE membrane has waterproofness, high filterability, good high temperature resistance and corrosion resistance.
[0096] The same performance test as in Example 1 was performed and the results were as follows.
[0097]
[0098] According to the results in the above table, the comprehensiveness of the PTFE membrane in this example is not as good as that of the PTFE modified separation membrane of the present invention, especially the pore size is too large. Although it can filter particulate matter, it has poor filtering performance for microorganisms and does not have actual antibacterial ability.
[0099] In addition, the freezing test was also carried out. The average initial setting time of the first test was 26.9 s, and the average final setting time was 96.6 s. After 20 tests, the average initial setting time of the sample membrane was 10.1 s, and the average final setting time was 33.2 s. It can be seen that the commercially available PTFE membrane basically does not have good antifreeze ability and anti-freeze aging ability.
[0100] Comparative Example 5: Based on the room temperature (20±1°C) performance tests of Examples 1 to 3 and Comparative Examples 1 to 4, the PTFE modified separation membrane prepared in Example 2 and the commercially available PTFE membrane used in Comparative Example 4 were further subjected to low temperature filtration tests. The low temperature filtration tests were conducted at 2 to 4°C, and the membrane materials were subjected to the same porosity test, membrane flux test, and hard water filtration characterization as in Example 1. The characterization results are shown in the following table.
[0101]
[0102] From the above characterization results, the PTFE modified separation membrane of the present invention is also particularly suitable for water filtration under low temperature conditions. Under low temperature conditions, the PTFE modified separation membrane of the present invention can almost completely maintain the original performance and the original filtering and softening water effects, while the commercially available PTFE does not have good antifreeze and low temperature resistance, and the membrane material is easily damaged and / or blocked under low temperature conditions, resulting in a decrease in the porosity of the membrane material, a decrease in the membrane flux, and a subsequent decrease in the filtering effect. It can be seen that it is suitable for use in cold northern regions.
Claims
1. A method for preparing a PTFE modified separation membrane for fluid purification, characterized in that: The method comprises: 1) Taking the raw material and molding it into a precursor film; 2) modifying the precursor film with an ammonium salt solution to obtain a modified film; 3) The modified membrane is preheated at 140-160°C for 15-25 min and subjected to biaxial stretching and heat treatment, and then subjected to gas laser etching to obtain a PTFE modified separation membrane; Step 1) The raw materials include polytetrafluoroethylene, carbon fiber, silver powder and additives; The auxiliary agent is an isoparaffin solvent; The polytetrafluoroethylene, carbon fiber and silver powder are mixed in a mass ratio of 10: (0.5-1.0): (0.1-0.5); The isoparaffin solvent is Isopar H additive, and the dosage is 0.1-0.3 g / g polytetrafluoroethylene; Step 2) Before the precursor film is modified, 0.2-0.4 mol / L aniline solution and water are mixed in a volume ratio of 1: (20-30) to form a mixed solution, and the mixed solution is used for infiltration treatment; Step 2) the ammonium salt solution is a 0.40-0.58 g / mL ammonium persulfate solution; Step 3) The gas laser etching process is as follows: The film was processed with a 10-20 W carbon dioxide laser; The control parameters during the gas laser etching process are as follows: laser scanning speed of 1 to 5 mm / min, scanning spacing of 3 to 8 μm, processing accuracy of ±20 μm, repetition frequency of 1 to 5 kHz, nitrogen and / or argon assist, and Z-axis offset of -5 to 0 mm.
2. The method for preparing a PTFE modified separation membrane for fluid purification according to claim 1, characterized in that: Step 1) The raw materials are mixed, heated and melted at 330-370°C, and then compression molded at a pressure of 2.4-7.0 MPa.
3. The method for preparing a PTFE modified separation membrane for fluid purification according to claim 1, characterized in that: Step 3) The biaxial stretching process is carried out at 200-240°C, with a rate of 230-280 mm / min for transverse and longitudinal biaxial stretching, respectively, and the stretching ratio is ≤4 times.
4. The method for preparing a PTFE modified separation membrane for fluid purification according to claim 1, characterized in that: Step 3) The heat treatment is performed at 240-280° C. for 10-20 min.
5. A PTFE modified separation membrane for fluid purification obtained by the method according to any one of claims 1 to 4.
Citation Information
Patent Citations
Inorganic nanomaterial and PTFE (polytetrafluoroethylene) hybrid hydrophobic membrane for seawater desalination
CN107321198A
PTFE modified separation membrane for fluid purification and preparation method of PTFE modified separation membrane
CN118512931A